Preserved Pancreatic β-Cell Development and Function in Mice Lacking the Insulin Receptor-Related Receptor - Kitamura, Tadahiro (American Society for Microbiology, 2001)
Receptors of the insulin/insulinlike growth factor (IGF) family have been implicated in the regulation of pancreatic β-cell growth and insulin secretion. The insulin receptor-related receptor (IRR) is an orphan receptor of the insulin receptor gene (Ir) subfamily. It is expressed at considerably higher levels in β cells than either insulin or IGF-1 receptors, and it has been shown to engage in heterodimer formation with insulin or IGF-1 receptors. To address whether IRR plays a physiologic role in β-cell development and regulation of insulin secretion, we have characterized mice lacking IRR and generated a combined knockout of Ir and Irr. We report that islet morphology, β-cell mass, and secretory function are not affected in IRR-deficient mice. Moreover, lack of IRR does not impair compensatory β-cell hyperplasia in insulin-resistant Ir(+/−) mice, nor does it affect β-cell development and function in Ir(−/−) mice. We conclude that glucose-stimulated insulin secretion and embryonic β-cell development occur normally in mice lacking Irr.